CULTURAL COMMUNICATION IN BUGIS SOCIETY IN PROCESS OF MARRIAGE CUSTOMS IN PANGKEP REGENCY - Hadawiah; Zelfia (Jurnal Komunikasi dan Bisnis, 2023)
Cultural communication in the Bugis community in the customary process of marriage in Pangkep Regency is a marriage first carried out in the procession as a tradition, customs and characteristics of the region, as well as the identity of the community in describing themselves. The purpose of this study is to find out how cultural communication in the tradition of the community in Bugis in the district in Pangkep. The theory used in this research is Herber Blumer symbolic interaction, this theory emphasizes more on human interaction on the meaning and symbols and meanings that exist in an object. The research method used is the phenomelogical research method. The results of the study that cultural communication in the customary process of marriage in the Bugis Pangkep community in South Sulawesi passed three stages, namely the stage before the marriage, the marriage stage and the stages after the wedding which that humans perform actions based on the meanings that exist in something. The first stage is after marriage. In this process the meaning can be obtained for the social interactions carried out by others, obtained at the second stage of the marriage stage, and the third stage of the stage after marriage. The meaning of perfected is obtained after social intraction is ongoing. The meaning of social intraction as a society that has values in every activity in the customs of marriage as cultural communication for the next generation.